Literature Review: Pengaruh Enzim ALDH2 dalam Detoksifikasi Alkohol terhadap Sirosis Hati - Anindia Istifara; Abdul Rohim Tualeka; Sahrir Sillehu (Media Gizi Kesmas, 2023)
Background: Ethyl alcohol or also known as ethanol is organic compound and one of the active substances that is often abused by human. Currently alcohol misuse yhat cause health problems become a global issue. Alcohol has toxic effect to the body. Some disease caused by alcohol consumption such as alcoholic liver disease. The liver as main organ in the binding of chemical substances (detoxification) will occur fatty liver, cirrhosis, or even liver function damage if alcohol level that accumulate in the liver is excessive. Objectives: The purpose of the study is to analyzed the effect of ALDH2 enzyme on alcohol detoxification process in alcoholics. Methods: This research study used literature review method on previous studies with similar topic. The articles were obtained from Google Scholar, Science Direct, and PubMed that published in 2013-2023 by applying inclusion and exclusion criteria so the article that fulfilled criteria could be analyzed. Results: The result of the literature review from 5 articles showed that the ALDH2 enzyme had a role in alcohol detoxification process. This enzyme was inhibitor for the rate of acetaldehyde metabolism which had cytotoxic and carcinogenics effect. Excessive amount of alcohol, especially with ALDH2 defficiency caused accumulation of acetaldehyde in human body that could increase the risk of liver cirrhosis Conclusions: ALDH2 levels in human body have an influence on the occurrence of liver cirrhosis in alcoholic.